The effect of job satisfaction on the level of productivity among government health sector nurses in Riyadh: A study of its application to Al-Iman General Hospital in Riyadh - Al-Zoghaibi, Saleh Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
The impact of job satisfaction on the level of productivity among nurses in the government health sector in Riyadh. The study also aims to identify the level of job satisfaction and the level of productivity among nurses at Al-Iman General Hospital in Riyadh. The study also contributes to improving the productivity of nurses in the health sector, and thus raising the quality and efficiency of Provided health services. The study used the analytical descriptive approach to achieve its objectives. The study sample consisted of (173) nurses (male - female) working at Al-Iman General Hospital. The study used the questionnaire as a data collection tool. Based on the above, the study reached a number of results, the most important of which is that the study individuals agree with a degree of agreement on the level of job satisfaction in the dimension of status and appreciation, with an average of (4.08). Where the averages of their agreement on the dimension ranged between (4.42 to 3.78), which are averages located in the fourth and fifth categories of the five-scale categories, which indicate (strongly agree - agree) on the study tool, which explains the homogeneity in the approval of the study individuals on the status and appreciation dimension. The results also showed that the study sample individuals strongly agree with the productivity level of the Al-Iman General Hospital nurses in Riyadh, with an average of (4.43 out of 5.00), which is an average that falls in the fifth category of the five-scale categories (from 4.21 to 5.00), which is the category that indicates the “I agree” option. strongly on the study tool. The study concluded that there is a direct positive statistically significant relationship at the level of significance (0.01) between job satisfaction and the level of productivity. In light of the results, the study recommends the need to pay attention to all factors of job satisfaction because of its effective role in raising the productivity level of employees in general, and nurses in particular. And the need to pay attention to improving the salaries of nurses, and the development of a specific system and mechanism for the system of material and moral incentives, as they have a significant impact on increasing the level of productivity among nurses.
Keywords: job satisfaction; level of productivity; health sector nurses; Al-Iman General Hospital; Riyadh